How to Account for Asymmetries in Deliberative Dialogues; Comment on "Evaluating Public Participation in a Deliberative Dialogue: A Single Case Study" - Jaime Jiménez-Pernett (Kerman University of Medical Sciences, 2023)
In health policy-making, various deliberative mechanisms can be used to engage the members of the public in exploring what might be a reasonable course of action. Scurr et al take power dynamics into consideration to analyse a deliberative dialogue involving stakeholders with diverse points of view. Given such asymmetries at play, the conclusions of deliberations could be biased. Scholars would benefit from guidance on designing and evaluating deliberative processes. This commentary aims to broadly reflect on the possible sources of power and information asymmetries in deliberative dialogues, and to bring the biographical resources approach to deal with such asymmetries.